México ¿la dictadura perfecta? - Rocío Ruiz Lagier (Les Cahiers ALHIM)
During the twentieth century, many countries of Latin America suffered military dictatorships or authoritarian regimes, however, during this time Mexico was projected as a democratic and peaceful country. However, in the history of the country there have been painful events that are not only not conform the oficial history, but also are not part of collective memory. A clear example is the so-called dirty war of the seventies, which resulted in hundreds of dissappeared persons who are not recognized today in political discourse, nor in the social imaginary. In this article, I am interested in analyzing the way different narratives unfold about the recent past, where oblivion has been a substantial element of internal politics. My interest is to show how this image of a peaceful and democratic country has been built, despite the fact that the country lived more than 70 years governed by the same party that controlled everything, and did so in the hands of one of the institutions that has played a relevant and permanent role in the modern history of country: the army. I think it is important to analyze it, not only as historical exercise, but as an analysis of the way thay in which mexican society relates to its past and thats impacts the current memory construction process.